A Comparative Study between Conventional Diaphragmatic Breathing Exercise and Virtual Reality-based Diaphragmatic Breathing Exercise on Quality of Life in Chronic Obstructive Pulmonary Disease Patients: A Randomized Control Trial - Sridhar Shirodkar; Medha Deo (Archives of Medicine and Health Sciences)
Background and Aim: Breathing exercise is an exercise intended to promote effective and healthy breathing and breathing control. Virtual reality (VR) is defined as a computer-generated simulation, such as a set of images and sounds that represent a real place or situation that can be interacted within a seemingly real or physical way by a person using special electronic equipment. Breathing exercises with VR have shown benefits over conventional diaphragmatic breathing exercises in normal individuals in many new studies. We propose the use of a novel VR-based approach as a respiratory biofeedback to improve breathing patterns in chronic obstructive pulmonary disease (COPD) patients, decrease their work of breathing, and improve breathing control. Materials and Methods: In a randomized controlled study involving 72 COPD patients divided into two groups of 36 in each, the control and experimental groups performed a short 5 min breathing exercise for 6 consecutive days. In experimental group patients performed breathing exercise with VR goggles while in controls they performed without VR goggles. Results: Both the control and experimental groups showed improved changes in vitals and better quality of life, but not statistically as significant when compared to each other. Conclusion: Future studies need to address the long-term effects and stability of the results with a larger sample size, compare the approach with the existing treatments, and make the required smaller changes to the program for better outcomes.